2016
DOI: 10.1371/journal.pone.0167289
|View full text |Cite
|
Sign up to set email alerts
|

Biological Markers for Pulpal Inflammation: A Systematic Review

Abstract: Background and ObjectivePulpitis is mainly caused by an opportunistic infection of the pulp space with commensal oral microorganisms. Depending on the state of inflammation, different treatment regimes are currently advocated. Predictable vital pulp therapy depends on accurate determination of the pulpal status that will allow repair to occur. The role of several players of the host response in pulpitis is well documented: cytokines, proteases, inflammatory mediators, growth factors, antimicrobial peptides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(189 citation statements)
references
References 107 publications
5
170
0
14
Order By: Relevance
“…As a result, the development of new pulp tests and chairside assays of potential prognostic indicators (disease biomarkers) should be a focus for translational research (Swedish Council on Health Technology Assessment , Rechenberg et al . , Ballal et al . ).…”
Section: Consensus‐based Recommendationsmentioning
confidence: 99%
“…As a result, the development of new pulp tests and chairside assays of potential prognostic indicators (disease biomarkers) should be a focus for translational research (Swedish Council on Health Technology Assessment , Rechenberg et al . , Ballal et al . ).…”
Section: Consensus‐based Recommendationsmentioning
confidence: 99%
“…Potentially discriminatory biomarkers have been identified, which could potentially set an inflammatory threshold above which the pulp is not viable (Rechenberg et al . , Zanini et al . ); however, at present biomarkers are not specific enough to predictably dictate treatment (Zehnder et al .…”
Section: Reviewmentioning
confidence: 99%
“…A quantitative analysis (the actual number of inflamed cells, inflammatory markers) and a qualitative analysis have been described and correlated to caries depth, caries proximity to the pulp and the inflammatory state of the pulp (McLachlan et al 2003). Potentially discriminatory biomarkers have been identified, which could potentially set an inflammatory threshold above which the pulp is not viable (Rechenberg et al 2016, Zanini et al 2017; however, at present biomarkers are not specific enough to predictably dictate treatment (Zehnder et al 2011). Further clinical studies investigating molecularbased assays are required to develop reliable diagnostic tools and better reproducibility.…”
Section: Pulp Inflammation and In Situ Diagnosismentioning
confidence: 99%
“…A systematic review demonstrated that pulpitis was induced by immunocompetent tissues that ultimately result in the release of mediators, which in turn trigger a series of inflammatory events and an attempt to initiate repair (Rechenberg et al . ). It is thus evident that pulp repair is closely related to the inflammatory response.…”
Section: Discussionmentioning
confidence: 97%
“…If the microbial stimulus is removed, mesenchymal stem cells dormant in the pulp are activated and migrate to form new dentine, then resolution of pulpitis and tissue repair occurs (Smith et al 1995a,b); however, if the stimulus is untreated, it will result in progressive inflammatory reactions in the pulp until pulp necrosis. A systematic review demonstrated that pulpitis was induced by immunocompetent tissues that ultimately result in the release of mediators, which in turn trigger a series of inflammatory events and an attempt to initiate repair (Rechenberg et al 2016). It is thus evident that pulp repair is closely related to the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%